2020
DOI: 10.1186/s12884-020-02874-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in perceived knowledge about childbirth among pregnant women participating in the Senses of Birth intervention in Brazil: a cross-sectional study

Abstract: Background: Senses of Birth (SoB) is a health education intervention in Brazil that aims to reduce unnecessary cesareans in the country by providing information on reproductive rights, benefits and risks of childbirth, and use of intrapartum evidence-based practices (EBP) which are recommended by the World Health Organization (WHO) to improve childbirth outcomes and satisfaction. This study evaluates the impact of the SoB on pregnant women's perceived knowledge about normal birth (NB), cesarean, and use of EBP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 73 publications
2
16
0
3
Order By: Relevance
“…In Brazil, women, especially those with low socioeconomic backgrounds, do not traditionally prepare themselves for labor, and this may have interfered with their understanding of the questionnaire statements. A recent study carried out in Brazil showed that knowledge about the type of birth and the use of evidence-based practices during childbirth was low among women with characteristics similar to those of our study sample [ 35 ].…”
Section: Discussionmentioning
confidence: 62%
“…In Brazil, women, especially those with low socioeconomic backgrounds, do not traditionally prepare themselves for labor, and this may have interfered with their understanding of the questionnaire statements. A recent study carried out in Brazil showed that knowledge about the type of birth and the use of evidence-based practices during childbirth was low among women with characteristics similar to those of our study sample [ 35 ].…”
Section: Discussionmentioning
confidence: 62%
“…The group of women who participated in this study can be identified as a group of well-informed women for the EBP, Normal Birth, and Cesarean knowledge domains. The women also showed improved awareness of their reproductive rights and choices after participating in the SoB intervention [ 41 ]. Access to quality information during prenatal care increased women’s self-efficacy and perceived control [ 37 , 52 54 ], allowing women to question unnecessary interventions, move away from exclusively medical-centered care, and avoid the repetition of a TMTS model.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived Knowledge. The perceived knowledge variables were grouped into three different domains, based on the results of factor analysis of a previous study [ 41 ]. The domains are: 1) EBP Knowledge, 2) Normal Birth Knowledge, and 3) Cesarean Knowledge.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations